Areal Convergence in Eastern Central European Languages and Beyond - Szucsich, Luka; Kim, Agnes; Yazhinova, Uliana (Linguistik International, 2020)
This book assembles contributions dealing with language contact and areal linguistics. The goal of the book is to investigate linguistic convergence in Europe with a strong focus on the languages of Eastern Central Europe which show many remarkable similarities. The focus is put on a methodical and empirical component in the investigation of two or more languages in the context of possible language contact phenomena. Languages of Eastern Central Europe and adjacent parts of Europe use a considerable amount of common vocabulary due to the transfer of loanwords during a long period of cultural contact. But they also share several grammatical features-phonological, morphological and syntactic ones. This book tackles lexical and grammatical phenomena in language contact situations. The authors take up diachronic, synchronic and language acquisitional perspectives, and discuss methodological problems for the field.